Relevansi Desain Tata Ruang Anak Terhadap Kemampuan Literasi Anak Di Dinas Perpustakaan Dan Kearsipan Kota Padang Panjang - Cut - Afrina; Saifuddin Rasyid; Rahma Dani; Syifa Salsabila; Ulfa Dwi Lara (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This article aims to describe the children's spatial design which includes: the placement of shelves, colors, furniture, lighting, and room area in the children's service room at the library service, and the archives of the city of Padang Panjang. A library must pay attention to the interior design of the library because this can support the literacy skills of users, one of which is children. Library interior design is a way of arranging the interior layout of a library building, which functions as a container for all activities and activities in the library by creating a comfortable and safe atmosphere and image of the space by paying attention to the needs of the individuals in it without neglecting aesthetic factors. Where the design will be by the expectations of users and librarians to improve children's literacy. Literacy can be interpreted as the ability to read, write, speak, and solve. To make children feel comfortable in the library room, a librarian must pay attention to the spatial design where this spatial design makes children feel comfortable and safe. Which is when children feel comfortable and safe, they can automatically increase literacy activities